Gradient hydrogels based on photo-initiated polymerization-induced self-assembly - Yingchu Zhou; Ziqi Liu; Yi Zeng; Li Luo; Jie Chen; Diyuan Zheng; Zhao Wu; Chao Lang (Giant)
Gradient materials enable performance optimization by adjusting composition or structure across one or more dimensions while minimizing interfacial incompatibility. However, current preparation procedures are often complicated, requiring multiple steps and complex post-processing. In this study, we report the fabrication of a unidirectional mechanical gradient hydrogel via a one-pot synthesis enabled by reversible addition-fragmentation chain transfer (RAFT)-mediated polymerization-induced self-assembly (PISA). Through concurrent photo-initiated RAFT polymerization and macro-CTA end-group cleavage, compositional and structural gradients were simultaneously created based on the distance from the light source. The near-light region displays a structure of disordered spheres primarily composed of triblock copolymer, while the far-light region features bicontinuous structure with a higher homopolymer content. This gradient design results in significantly different mechanical properties such as strength, resilience, modulus, and loss factors across the hydrogel. Moreover, gradient hydrogel demonstrates exceptional impact resistance, where the soft region efficiently absorbs and dissipates energy while the hard region provides structural support. This study highlights the potential of PISA in developing high-performance gradient materials with tailored mechanical properties, offering promising applications in protective sports equipment, energy absorption systems, soft robotics, and biomedical implants.